El sistema de ayuda al usuario de un catálogo en línea de acceso público: delimitación teórica y propuesta práctica - Moscoso Castro, Purificación; García, Francisco (Documentación de las Ciencias de la Información, 2007)
In recent years, research on online public access catalogs has been directed at improving two different areas: increasing the potential of information retrieval and also improving the human-system relationship by creating friendlier and more intuitive user interfaces. Regarding the latter, the specific development of user online help systems has contributed to the creation of some simple and useful tools. However, there is a group of theorists that holds that help systems should only be utilized to aid the user in operating the OPAC, while others offer the inclusion of new information technologies thereby increasing user satisfaction. The objective is focused on theoretically demarcating a definition and operational capacity of superior systems, 3rd generation OPAC that include on-line help systems, and consequently proposing a path that resolves the daily problems that a user encounters in the use of these on-line catalogs.